2011
DOI: 10.4103/2230-8210.81946
|View full text |Cite
|
Sign up to set email alerts
|

A young lady with swelling and stiffness of calf muscles

Abstract: Hypothyroidism causes a variety of changes in the body. Though uncommon, hypothyroidism can present as myopathy. Hoffman's syndrome is a specific, rare form of hypothyroid myopathy, which causes proximal weakness and pseudohypertrophy of muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
(8 reference statements)
0
3
0
4
Order By: Relevance
“…This suggests that continuous, spontaneous electrical activity of muscle could cause a true hypertrophy. [11][12][13][14][15][16] Kiran et al 17 reported a case of Hoffman syndrome, a rare form of hypothyroid myopathy, with proximal weakness and pseudohypertrophy of muscles, thought to be secondary to accumulation of glycosaminoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that continuous, spontaneous electrical activity of muscle could cause a true hypertrophy. [11][12][13][14][15][16] Kiran et al 17 reported a case of Hoffman syndrome, a rare form of hypothyroid myopathy, with proximal weakness and pseudohypertrophy of muscles, thought to be secondary to accumulation of glycosaminoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…El retraso en la contracción y relajación muscular puede deberse a la redistribución de fibras de contracción rápida a contracción lenta. [3][4] Los grupos musculares más comúnmente involucrados son: la lengua y las extremidades superiores e inferiores. 2 En la figura 1 se aprecia la hipertrofia muscular a nivel de brazo, muslos y pantorrillas del paciente al ingreso, y la disminución de volumen luego de 35 días de tratamiento sustitutivo hormonal.…”
Section: Discussionunclassified
“…Las manifestaciones de hipotiroidismo que llevan a distintos tipos de neuropatía y miopatía son responsables únicamente del 5% de todas las miopatías adquiridas. 4 Por lo que el diagnóstico diferencial debe incluir las principales causas de debilidad muscular, (figura 2).…”
Section: Discussionunclassified
“…True myopathy is a primary muscle involvement characterized by slowed muscle contraction and relaxation, muscle pain, proximal muscle weakness, sluggish ankle jerks and absence of sensory involvement 6 . Pain on muscle exertion is due to defective carbohydrate metabolism 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Literature search shows that the prominence of muscle symptoms correlates fairly closely with the degree and duration of hypothyroidism 6 and the serum CK level may be elevated in hypothyroidism: and can be an important differential diagnosis for raised serum CK. Case reports 6,7 shows that hypothyroidism can present with muscular symptoms alone with minimal or without any classical symptoms and signs of hypothyroidism.…”
Section: Introductionmentioning
confidence: 99%